2021
DOI: 10.1093/icesjms/fsab153
|View full text |Cite
|
Sign up to set email alerts
|

Five centuries of cod catches in Eastern Canada

Abstract: The fishery for Northern Atlantic cod (Gadus morhua) off Newfoundland and Labrador, Eastern Canada, presents the most spectacular case of an exploited stock crashed in a few decades by an industrial bottom trawl fishery under a seemingly sophisticated management regime after half a millennium of sustainable fishing. The fishery, which had generated annual catches of 100000 to 200000 tonnes from the beginning of the 16th century to the 1950s,  peaked in 1968 at 810000 tonnes, followed by a devastating collapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The outcome of our study is consistent with empirical observations of overfished cod stocks, cautioning that fishing can be a strong selective agent, especially in populations that undergo uninterrupted heavy exploitation for several decades and can lead to a fitness deficit of heavily overfished stocks [ 28 , 46 , 53 ]. While some commercially overexploited stocks such as North Sea cod stock are showing signs of recovery [ 54 ], stocks such are Northern cod stocks struggle to recover their biomasses [ 13 ]. The results presented here warn that the abundance recovery to pre-fishing condition does not necessarily mean that the across-generational fitness has recovered as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome of our study is consistent with empirical observations of overfished cod stocks, cautioning that fishing can be a strong selective agent, especially in populations that undergo uninterrupted heavy exploitation for several decades and can lead to a fitness deficit of heavily overfished stocks [ 28 , 46 , 53 ]. While some commercially overexploited stocks such as North Sea cod stock are showing signs of recovery [ 54 ], stocks such are Northern cod stocks struggle to recover their biomasses [ 13 ]. The results presented here warn that the abundance recovery to pre-fishing condition does not necessarily mean that the across-generational fitness has recovered as well.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructions from historical records have demonstrated that some of today's commercially fished stocks represent merely a remnant of once highly abundant populations [ 12 , 13 ]. For example, cod fisheries date back to the pre-Mesolithic Stone Age [ 14 ], but intense fishing practices have depleted most stocks only in recent decades, with some stocks collapsing to less than 5% of their pre-industrial fishing values [ 13 ]. As a consequence, some stocks may have passed their tipping point of recovery as reflected by the Allee effects [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). During this period, although exact abundance and biomass estimates are difficult, the landings of Northern cod (to >800 000 t reported in 1968), and previous population modelling, leave little doubt that cod were very abundant across a wide age structure from northern Labrador to the North Cape of the Grand Bank, with the stock likely comprising several million tonnes (e.g., Baird and Bishop 1989;Rose 2004;DFO 2021a;Schijns et al 2021).…”
Section: Stanza 1: the 1960s (And Earlier)mentioning
confidence: 94%
“…Fortunately, after twenty years, with much scientific research work done on this problem, it is much better understood. Therefore, there are multiple examples of mismanagement of fisheries resources, with regrettable consequences leading to the over exploitation of many fish resources and their consequences in their environment [9][10][11][12]. In the present paper, populations are evaluated by reconstructing the age structure of each of the years analyzed.…”
Section: Introductionmentioning
confidence: 99%